2020
DOI: 10.1111/jfpp.14965
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of microencapsulated Lactobacillus rhamnosus GG in hawthorn berry tea with flaxseed mucilage

Abstract: Viability of probiotics could be affected by the production process, storage in the food matrix, and the digestion processes in the human body. This study aimed to determine the storage stability of microencapsulated Lactobacillus rhamnosus GG with flaxseed mucilage in hawthorn berry tea. The different formulation was used to microencapsulate L. rhamnosus GG with or without the addition of flaxseed mucilage in the wall and core material. The L. rhamnosus GG microencapsulated with alginatepectin-flaxseed mucila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…These results indicated that the L. rhamnosus GG was sensitive to the conditions in strawberry nectar and during the gastrointestinal transit. These findings were in agreement with those reported by Lai et al (2020) where free L. rhamnosus GG cells in hawthorn berry tea reduced by 100% after exposure to gastrointestinal for 120 min. Another report by Chávarri et al (2012) found 100% reduction of free Lactobacillus gasseri and Bifidobacterium bifidum cells after exposing to gastrointestinal.…”
Section: Viability Of Free and Encapsulated L Rhamnosus Gg In Strawberry Nectar After Storagesupporting
confidence: 93%
“…These results indicated that the L. rhamnosus GG was sensitive to the conditions in strawberry nectar and during the gastrointestinal transit. These findings were in agreement with those reported by Lai et al (2020) where free L. rhamnosus GG cells in hawthorn berry tea reduced by 100% after exposure to gastrointestinal for 120 min. Another report by Chávarri et al (2012) found 100% reduction of free Lactobacillus gasseri and Bifidobacterium bifidum cells after exposing to gastrointestinal.…”
Section: Viability Of Free and Encapsulated L Rhamnosus Gg In Strawberry Nectar After Storagesupporting
confidence: 93%
“…Researchers have been exploring probiotics incorporated in a different types of fruit juices (Acevedo-Martínez et al, 2018;Nancib et al, 2009;Nualkaekul & Charalampopoulos, 2011;Valero-Cases et al, 2017). Besides fruit juice, other nondairy beverages such as vegetable, tea, flower extract, and herbal extract; have also been explored to be potential functional beverages with the incorporation of probiotics (Lai et al, 2020b;Naga Sivudu et al, 2016;Yee et al, 2019).…”
Section: Nondairy B E Ver Ag E S a S Prob Iotic C Arriermentioning
confidence: 99%
“…Previous studies had also reported that mucilage from basil seed (Wongputtisin & Khanongnuch, 2015), psyllium husk seed (Esmaeilzadeh et al, 2016), and bush mint seed (Mueller et al, 2017) showed high prebiotic potential on stimulating the growth of probiotics. Flaxseed is composed of about 11-15% of mucilage and it consists of a mixture of rhamnogalacturonan I and arabinoxylan, where the latter has been found to have prebiotic activity (Lai et al, 2020b;Lai et al, 2020c;Naran et al, 2008;Pastell et al, 2009;Singer et al, 2011). In addition, chia seed contains about 5-6% of mucilage that is made up of β-D-xylopyranosyl, α-D-glucopyranosyl, and 4-O-methyl-α-Dglucopyranosyl-uronic acid unit in the ratio 2:1:1 (Muñoz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%